Spirit Moderasi Beragama dalam Pluralitas Multi-Agama (Studi Living Qur’an Desa Buntu Kejajar Wonosobo) - Hami, Widodo (Pascasarjana IAIN Sultan Amai Gorontalo, 2024)
This research reveals the results of research by combining Al-Qur'an studies with socio-religious phenomena. This article will answer the question of how the spirit of religious moderation is in a plurality of multi-religious villages by collaborating with Al-Qur'an studies. The methodology used is a qualitative field-based methodology with the research object of Buntu Village, Kejajar District, Wonosobo Regency, using phenomenology as its approach. With this methodology and approach, this study succeeded in uncovering findings that the spirit of religious moderation implemented by the Buntu community refers to the three pillars of moderation values that have been formulated by the Ministry of Religion as a counter-narrative form of intolerance and exclusivism in religion which includes a commitment to nationalism, tolerance, and anti-religion. violence. The Buntu community bases their spirit of moderation on QS Al-Baqarah: 256 and QS Al-Kafirun: 6 which explicitly states that there is no compulsion in choosing a religion.